Store Atmosphere, SERVQUAL and Consumer Loyalty: Case Study of Excelso Coffee Shop - Purwadi, Purwadi; Devitasari , Bella; Caisar Darma, Dio (SEISENSE (PRIVATE) LIMITED, 2020)
Purpose- With competitors, making business people must continue to evaluate the marketing strategy carried out and understand consumer behavior, especially from the coffee shop. The study aims to present the relationship between Store Atmosphere, SERVQUAL, and Consumer Loyalty in Excelso (Big Mall, Samarinda City). Design/Methodology- We conduct online surveys (instrumental social networking sites). The sample of this study was based on purposive sampling. There were total 98 participants. The study hypotheses were assessed with the OLS model. Findings- We find that there is a significant positive effect of the Store Atmosphere variable on SERVQUAL and SERVQUAL on Consumer Loyalty. Meanwhile, the relationship between Store Atmosphere and SERVQUAL variables is positive-insignificant. Practical Implications- With this study, it can create a sense of curiosity to conduct further research, namely by holding interviews or distributing a broader questionnaire to obtain maximum results.